Association between exclusive or dual use of combustible cigarettes and heated tobacco products and depressive symptoms - Bo Gyeong Lee; Haein Lee; Namhee Kim (PLoS ONE, 2025)
Purpose Despite the advent of heated tobacco products (HTPs), their relationship to mental health remains unclear. This study aimed to determine associations between the use of combustible cigarettes (CCs) and HTPs with depressive symptoms. Methods This descriptive-analytical cross-sectional study was conducted in March 2023. Using the 8th Korea National Health and Nutrition Examination Survey, 5,349 adults aged 19 years or older were classified into four groups: non-users, CC-only users, HTP-only users, and dual users. Relationships between exclusive or dual use of CCs and HTPs and depressive symptoms were analyzed using item scores and total scores of the Patient Health Questionnaire-9 (PHQ-9). To examine associations between exclusive or dual use of CCs and HTPs and depressive symptoms, a multinomial regression analysis was performed using the PHQ-9 total score. Results HTP-only users had the highest proportion of those with anhedonia and depressed mood. CC-only users had the highest proportion of individuals with trouble sleeping, while dual users had a higher proportion of those with fatigue and appetite problems. After adjusting for general characteristics, compared to non-users, CC-only users were more likely to have mild and moderate to severe depressive symptoms. HTP-only users and dual users were also more likely to have moderate to severe depressive symptoms. Conclusions All smokers have a higher risk of depression than non-smokers. Health care providers should closely monitor depressive symptoms, especially in HTP users and dual users of tobacco products.